2023
DOI: 10.1128/spectrum.02009-22
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Activity of Vaginal Lactobacilli on Bifidobacteria: from Concept to Formulation

Abstract: Bifidobacteria in the gut tract of infants play crucial roles in the prevention of gastrointestinal diseases and the maturation of the immune system. Consequently, strategies to trigger a bifidogenic shift in the infant gut are highly desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In this regard, we have previously demonstrated that the culture supernatants of vaginal lactobacilli, especially that of L. vaginalis BC17, can stimulate the growth of Bifidobacterium spp., likely due to the secretion of metabolites that can serve as substrates [18]. Instead, in the present work, we focused on L. vaginalis BC17 cells to further investigate the strain's capability to drive a bifidogenic shift in infants' gut.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, we have previously demonstrated that the culture supernatants of vaginal lactobacilli, especially that of L. vaginalis BC17, can stimulate the growth of Bifidobacterium spp., likely due to the secretion of metabolites that can serve as substrates [18]. Instead, in the present work, we focused on L. vaginalis BC17 cells to further investigate the strain's capability to drive a bifidogenic shift in infants' gut.…”
Section: Discussionmentioning
confidence: 99%
“…infantis DSM20088, B. longum subsp. infantis DSM20090, B. adolescentis DSM20083, B. adolescentis DSM20086, B. angulatum DSM20098) were purchased from DSMZ (Braunschweig, Germany) [18]. L. vaginalis and bifidobacteria were routinely cultured in de Man, Rogosa, and Sharpe broth (MRS, Difco, Detroit, MI, USA) supplemented with L-cysteine 0.05% (w/v) (Merck, Milan, Italy) at 37 • C, in anaerobic jars containing Gas-Pak EZ (Beckton, Dickinson and Co., Milan, Italy).…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
See 3 more Smart Citations